2022
DOI: 10.1002/wfp2.12037
|View full text |Cite
|
Sign up to set email alerts
|

Does exposure to weather variability deter the use of productivity‐enhancing agricultural technology? Evidence from Ethiopia

Abstract: This study examines how farm households' decision to use modern agricultural inputs is influenced by the weather variability using a household panel survey merged with long‐term historical weather data from Ethiopia. As a part of an effort to fill methodological gaps that are observed and anticipated in previous similar literature, this study employs a more flexible modeling approach under a multiagricultural technologies framework. Findings suggest that weather uncertainty reduces the probability and intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
(197 reference statements)
0
1
0
Order By: Relevance
“…According to Aggarwal et al ( 2018 ), between 2012 and 2020, CSV-related outcomes were reported across five CCAFS regions: Southeast Asia (16), South Asia (14), East Africa (12), West Africa (12), and Latin America (10). The adoption rate of improved agricultural technology, performance, and productivity in Ethiopia’s agriculture sector remains inadequate due to a lack of information on the technicality of available agriculture technologies and an insufficient supply of inputs (Berha, 2022 ; Suri & Udry, 2022 ; Yu & Nin-Pratt, 2014 ). A recent study found that CSA practices, such as improved crops, are being used in Africa to increase household income and food security (Ogunyiola et al, 2022 ; Suri & Udry, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Aggarwal et al ( 2018 ), between 2012 and 2020, CSV-related outcomes were reported across five CCAFS regions: Southeast Asia (16), South Asia (14), East Africa (12), West Africa (12), and Latin America (10). The adoption rate of improved agricultural technology, performance, and productivity in Ethiopia’s agriculture sector remains inadequate due to a lack of information on the technicality of available agriculture technologies and an insufficient supply of inputs (Berha, 2022 ; Suri & Udry, 2022 ; Yu & Nin-Pratt, 2014 ). A recent study found that CSA practices, such as improved crops, are being used in Africa to increase household income and food security (Ogunyiola et al, 2022 ; Suri & Udry, 2022 ).…”
Section: Introductionmentioning
confidence: 99%